Comprehensive Evaluation of Antifungal Activity of Argania spinosa (L.) Skeels kernels of the Hot and Cold Extraction and the Effect of Solvents Varying Polarities and the Heat Treatment on Yield and Activity Variance - Aziza Lfitat; Imad Ed-dahmani; Fatima Zohra Bousraf; Abdelhaq Belhaj; Tarik Ainane; Mustapha Taleb; Abdelkader Gourch; Abdelfattah Abdellaoui (Indonesian Food and Nutrition Progress, 2023)
A comparative antifungal efficacy study of argan kernels was performed using different solvent fractions obtained by the two extraction methods: cold extraction by maceration at room temperature (1) and hot extraction by Soxhlet apparatus (2). Results demonstrated that the two extraction methods induce different yields among each solvent used. Maceration promoted the maximum contents of crude extract in hexane (42.15%), diethyl ether (2.59%), dichloromethane (4.22%), and ethyl acetate (2.52%). Whereas the hot extraction yielded higher extractives in the case of methanol (22.97%) and water (5.88%) compared to cold extraction. The MIC values of the fractionated extracts obtained by maceration were in the range of 0.051 ± 0.002 and 0.223 ± 0.005 g/ml, whilst they were in the range of 0.101 ± 0.002 and 0.286 ± 0.005 g/ml for the Soxhlet extracts. According to total activity (TA) interpretation, dichloromethane was the most effective solvent to extract active antifungal components, revealing the strongest ability to suppress the growth of fungi at much lower MIC values (0.051 ± 0.002 to 0.156 ± 0.005 g/ml) than the rest of fractions. The effect of heating resulted in an increase of the MICs values of the Soxhlet extracts from 10 to 25 times higher than macerated ones, resulting in lower antifungal activity.